Studi Fitokimia Senyawa Aktif Ekstrak Batang Nelambo suon (Rubiaceae) - Rossardy, Marzella Dea; Muslihin, A.M.; Watora, Wahyuni; Budiyanto, Angga Bayu; Hardia, Lukman; Irwandi, Irwandi; Aponno, Alyssa Mileta; Utami, Hikmahtul Putri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Papua has high biodiversity with significant potential as a source of traditional medicinal plants, including Nelambo suon (Rubiaceae), which has been empirically used by local communities. However, scientific information regarding the active compounds in its stem bark remains limited. Objective: This study aimed to identify the secondary metabolite groups present in the ethanol extract of Nelambo suon stem bark through phytochemical screening. Methods: The research was conducted experimentally using the maceration method with 80% ethanol as the solvent. The stem bark simplicia was extracted and qualitatively screened for alkaloids, flavonoids, tannins, and saponins using specific reagents. Results: The results showed that the ethanol extract of Nelambo suon stem bark contained alkaloids, flavonoids, tannins, and saponins, indicated by characteristic color changes, precipitate formation, and foam production. Conclusion: These findings suggest that Nelambo suon stem bark is a potential source of bioactive compounds and may be further developed as a herbal medicinal material based on local wisdom.